(untitled) (Fiep Bulletin - online, 2015)
The present study it had as objective to stand out the importance of the physical evaluation in the pertaining to school physical education, despite the pertaining to school physical activities being of playful and educational character, the physical effort exists, that can be harmful when some student to present some morfofisiológic clutter. The main parameters of an evaluation had been analyzed how much its importance in diagnose of a group of students of average education. Through the application of anamnese, measured antropométricas, postural evaluation, physical tests and of the mensure of the corporal composition; it is that if it can diagnosis this sample, being able to restrict some exercises and/or physical activities, in accordance with the limitations physical and physiological of each individual, respecting the biological individuality and applying the best strategy to reach the improvement of the health and, consequently the improvement of the quality of life through the pertaining to school physical education. The used sample was of 297 adolescent students, of average education, in two schools of the state net in Rio De Janeiro. The used methodology was the elaboration of a physical and functional evaluation, consisting of one anamnese, measured antropométricas, subjective postural evaluation and some physical tests. In it analyzes of the results, it can be observed that the sample presented innumerable problems of health and postural. Soon, an awareness of the importance of the physical evaluation in diagnose of its pupils fits to the professionals of Physical Education, better to elaborate the adequate and promotional pertaining to school activities physical of the health.